Effects of quercetin supplementation on inflammatory factors and quality of life in post‐myocardial infarction patients: A double blind, placebo‐controlled, randomized clinical trial. (20th November 2020) - Dehghani, Fereshteh; Sezavar Seyedi Jandaghi, Seyed Hashem; Janani, Leila; Sarebanhassanabadi, Mohammadtaghi; Emamat, Hadi; Vafa, Mohammadreza
Abstract : Myocardial infarction (MI) is one of the leading causes of death in the world. Epidemiological studies have shown that dietary flavonoids are inversely related to cardiovascular morbidity and mortality. The study aimed to determine whether quercetin supplementation can improve inflammatory factors, total antioxidant capacity (TAC) and quality of life (QOL) in patients following MI. This randomized double‐blind, placebo‐controlled trial was conducted on 88 post‐MI patients. Participants were randomly assigned into quercetin ( n = 44) and placebo groups ( n = 44) receiving 500 mg/day quercetin or placebo tablets for 8 weeks. Quercetin supplementation significantly increased serum TAC compared to placebo (Difference: 0.24 (0.01) mmol/L and 0.00 (0.00) mmol/L respectively; p < .001). TNF‐α levels significantly decreased in the quercetin group ( p = .009); this was not, however, significant compared to the placebo group. As for QOL dimensions, quercetin significantly lowered the scores of insecurity (Difference: −0.66 (12.5) and 0.00 (5.55) respectively; p < .001). No significant changes in IL‐6, hs‐CRP, blood pressure and other QOL dimensions were observed between the two groups. Quercetin supplementation (500 mg/day) in post‐MI patients for 8 weeks significantly elevated TAC and improved the insecurity dimension of QOL, but failed to show any significant effect on inflammatory factors, blood pressure and other QOL dimensions.